Defining education: al-Farabi and Ibn Sina terminologies - Imdad, Muhammad; Hafidhuddin, Didin; Arif, Syamsuddin (Ibn Khaldun Journal of Social Science, 2019)
Contemporary debate on proper term of Islamic education has been long disputed. This disagreement is reflective of more profound and substantial problems besetting Muslims view, especially their leader, on what Islamic education is and its concomitants. One way to solve the problem, or at least to provide solid basis to analyze and then to answer the question, is to read our Islamic heritage on this theme. Unfortunately, as far as my limited knowledge goes, there is no one single unified discipline in Islamic tradition called education, understood in modern sense, although hints and sometime even extended discussion of some of its aspects can easily be found. Our task, therefore, is to reconstruct what we read and put it into today’s educational context of ours. This paper is meant to be small contribution along this line. It focuses on two prominent thinkers, representative of philosophical strand in Islamic tradition, al-Farabi and Ibn Sina. Justification of choosing them, other than the obvious influence of their ideas on later development of Islamic thought including education, is that their elaboration is marked by meticulousness, a quality often associated with philosophy. The approach adopted in this paper is to identify terms used by al-Farabi and Ibn Sina, which can be construed as education, and then to analyze them and put them within general context of modern education. The expected result is to recognize terms used in classical Islamic era to signify education and to ascertain which term is more proper.